ErgoVSM: A new tool that integrates ergonomics and productivity - Denisse Dominguez-Alfaro; Ismael Mendoza-Mu\~noz; Carlos Raúl Navarro-González; Mildrend Ivett Montoya-Reyes; Samantha E. Cruz-Sotelo; Olivia Yessenia Vargas-Bernal (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Identifying possible ergonomic risks generated by the implementation of Lean Manufacturing in organizations. Shows a need to integrate ergonomics and productivity indicators in process analysis, thus giving place to the ErgoVSM methodology, which is VSM (Value Stream Mapping) complemented with ergonomic analysis. Design/methodology/approach: This literature review aims to refer to the methodology and instruments used for its application, as well as the benefits obtained and the challenges that arise when applying it. Findings: This article presents a review of 26 publications regarding the ErgoVSM methodology. The ErgoVSM is mainly based on the VSM methodology developed by Rother & Shook that is most applied in the healthcare sector with ergonomic analysis instruments that focus on the physical and psychosocial factors of the workers. Originality/value: The review revealed that when using ErgoVSM, processes can be improved from the ergonomic perspective without negatively affecting productivity. Even though ErgoVSM requires more time for application compared to VSM, the value of the ergonomic data for decision making in process changes justifies the extra time.
Keywords: 650; ErgoVSM; VSM; Value Stream Mapping; ergonomics; human factors